Novel Enzyme-Free Multifunctional Bentonite/Polypyrrole/Silver Nanocomposite Sensor for Hydrogen Peroxide Detection over a Wide pH Range - Khouloud Jlassi (2583832) (2019)
Precise designs of low-cost and efficient catalysts for the detection of hydrogen peroxide (H2O2) over wide ranges of pH are important in various environmental applications. Herein, a versatile and ecofriendly approach is presented for the rational design of ternary bentonite-silylpropyl-polypyrrole/silver nanoarchitectures (denoted as BP-PS-PPy/Ag) via the in-situ photo polymerization of pyrrole with salinized bentonite (BP-PS) in the presence of silver nitrate. The Pyrrolyl-functionalized silane (PS) is used as a coupling agent for tailoring the formation of highly exfoliated BP-PS-PPy sheet-like nanostructures ornamented with monodispersed Ag nanoparticles (NPs). Taking advantage of the combination between the unique physicochemical properties of BP-PS-PPy and the outstanding catalytic merits of Ag nanoparticles (NPs), the as-synthesized BP-PS-PPy/Ag shows a superior electrocatalytic reduction and high-detection activity towards H2O2 under different pH conditions (from 3 to 10). Intriguingly, the UV-light irradiation significantly enhances the electroreduction activity of H2O2 substantially, compared with the dark conditions, due to the high photoelectric response properties of Ag NPs. Moreover, BP-PS-PPy/Ag achived a quick current response with a detection limit at 1 μM within only 1 s. Our present approach is green, facile, scalable and renewable. Other Information Published in: Sensors License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/s19204442